Physical properties of some unfilled resins employed in semiconductor packages. Issue 1 (1st January 2018) - Tuncer, Enis; Hernandez-Luna, Alex
Abstract : We have performed thermo-mechanical and electrical tests on epoxy resin samples used for semiconductor packaging applications. The reported resins are commonly used in Texas Instrument Incorporated products. The study was performed to better understand the influence of the resin system on physical properties of mold compounds, which are composed of mainly epoxy resin and inorganic filler particles. The results illustrated that the estimated glass transition temperatures, T g, for the three unfilled systems were lower than those observed in filled systems and reported by the supplier. Additional computer simulations performed using molecular dynamics yielded higher glass transition temperatures than the experimental ones, however, one needs to be cautious due to the time scales used in the simulations. The electrical conductivity values were obtained from the time domain measurements, and they illustrated that the materials have minor differences in their temperature-dependent conductivity below 130 ∘ C, while above T g formulation differences could be observed and correlated to thermo-mechanical measurements.